Reversible Video Watermarking Scheme using DWT-SVD for Data Integrity of Noisy Multimedia Data - Patil, Neha; V.R Udupi, Dr. (International Journal of Engineering and Technology, 2018)
In this paper DWT-SVD scheme is presented to achieve data integrity of noisy multimedia data. Spatial domain methods are simpler but prone to attacks. DWT offers simultaneous localization in time and frequency domain and SVD is powerful technology in matrix decomposition. As SVD is computationally expensive, this paper combines DWT and SVD. The proposed method modifies diagonal singular coefficients of LL sub-band. The overall system model consists of embedding algorithm at sender side and noise removal algorithm followed by extraction algorithm at receiver side. During transmission, there is a possibility of noise inclusion due to various sources. This degrades the watermarked video quality and affects watermark extraction at receiver side. To provide a solution to this problem, noise removal algorithm is implemented as a pre-processing step prior extraction algorithm. This provide quality multimedia data for data integrity detection in the watermark extraction process. Experimental results demonstrate significant improvement in quantitative measures PSNR, SSIM and CC values.Â